ANALYSIS OF THE PERCEPTION OF THE MILLENNIAL GENERATION'S INTEREST IN THE PROCESS OF USING M-BANKING AFTER REBRANDRING - Sari, Dessy Handa; Khairiyah, Nurul Musfirah; Surono, Prasetyo Indra; Dharmawan, Ida Bagus (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2024)
Human life is greatly influenced by the advancement of information technology. In the midst of a shift in people's lifestyles, banking businesses are turning to services that have a digital basis to increase industry competition and obtain potential target markets. To make transactions easier for customers, internet banking, SMS banking, mobile banking, automatic teller machines, and electronic data capture are some of the services provided. This resulted in an increase in revenue based on costs (Otoritas Jasa Keuangan, 2015) Currently, many banks are rebranding in M-Banking, The purpose of this study is to find out the influence of the convenience, benefits, attitudes and behavioral control of the millennial generation on the decision to use mobile banking services through interest after rebranding. The main data for this study comes from millennial customers who use mobile banking who have rebranded. Smart PLS 3.0 software is used to analyze Partial Least Square (PLS) data